KOLFU 2012 (The local and regional councils survey) - KOLFU 2012 - The local and regional councils survey - Karlsson, David; Gilljam, Mikael (University of Gothenburg, 2018)
KOLFU is a survey directed to all members of the 20 regional/county councils and 290 municipal councils in Sweden (in total about 13,500 individuals). KOLFU was conducted for the first time in 2008 and the second time in 2012. The total number of respondents in 2012 was 10,491.

KOLFU was administrated by researchers from University of Gothenburg, while the company Detector AB was responsible for the field work. The survey was carried out within the project "Swedish politicians [Svenska politiker]". Mikael Gilljam was the project leader and David Karlsson the project coordinator.

KOLFU comprise questions about the councillors' social background, attitudes towards political issues, views on democracy and political work in their own municipalities and regions.

Purpose:

The aim of KOLFU is to survey Swedish local and regional politicians' views on democracy and politics.

The KOLFU-survey was mainly conducted through a web-survey. The field work was carried out in the following way: In phase one, e-mail addresses to as many councillors as possible were assembled. In an e-mail, the respondents were given the opportunity to respond to the questionnaire on the Web. Councillors who lacked an e-mail address were sent a paper questionnaire by post. Councillors with e-mail addresses could also ask to be sent a postal questionnaire. Respondents received repeated reminders through e-mail, postal mail and via telephone.

KOLFU är en undersökning som riktar sig till samtliga fullmäktigeledamöter i Sveriges 20 landsting och 290 kommuner (totalt cirka 13 500 personer). KOLFU genomfördes för första gången 2008-2009 (KOLFU 2008) och andra gången 2012-2013 (KOLFU 2012). Antalet faktiska respondenter 2012 - exklusive bortfallet - var 10,491 .
KOLFU 2012 genomfördes av forskare vid Göteborgs universitet medan företaget Detector AB svarade för fältarbetet. Undersökningen genomfördes inom ramen för projektet Svenska politiker. Forskarteamet bestod av Mikael Gilljam (projektledare) och David Karlsson (projektsamordnare). I KOLFU ingår frågor om ledamöternas sociala bakgrund, deras åsikter i politiska frågor, deras syn på demokratins spelregler och det politiska arbetet i den egna kommunen och landstinget.

Syfte:

Kommun- och landstingsfullmäktigeundersökningen (KOLFU) genomförs för att undersöka svenska kommun- och landstingspolitikers syn på demokrati och politik.

KOLFU-undersökningarna genomfördes huvudsakligen som e-enkäter. Fältarbetet har varit upplagt på följande sätt: I en första fas samlades e-postadresser in till så många ledamöter som möjligt. I ett e-brev fick respondenterna därefter möjligheten att via en länk besvara enkätundersökningen på Internet. Ledamöter som saknar e-adress fick en postenkät till hemadressen. Det gällde även ledamöter som särskilt bad om att få besvara enkäten på detta sätt. Ledamöter som inte svarade fick upprepade påminnelser via e-post, brev och telefonsamtal.
Kommun- och landstingsfullmäktigeundersökningen (KOLFU) 2012
Keywords: local government policy; kommunalpolitik; political behaviour; politiskt beteende; democracy; demokrati; political parties; politiska partier; regional policy; regionalpolitik; politicians; politiker; representative democracy; representativ demokrati; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Political ideology; Politisk ideologi; Government, political systems and organisations; Regering, politiska system och organisationer; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Public Administration Studies; Studier av offentlig förvaltning